Evaluation of minimum volume standards for surgery in the Netherlands (2003–2017): A successful policy?. Issue 12 (December 2017) - Mesman, Roos; Faber, Marjan J.; Berden, Bart J.J.M.; Westert, Gert P.
Highlights: Dutch stakeholders alternated in taking the lead in volume-based policies. The number of low volume Dutch hospitals performing complex surgeries decreased. Research has shown improved outcomes as a result. Policy lessons: professionals in the lead, external pressure helps, volume remains controversial. Abstract: Purpose: To evaluate the introduction and implications of minimum volume standards for surgery in Dutch health care from 2003 to 2017 and formulate policy lessons for other countries. Setting: Dutch health care. Principal findings: Three eras were identified, representing a trust-and-control cycle in keeping with changing roles of different stakeholders in Dutch context. In the first era 'regulated trust' (2003–2009), the Dutch Inspectorate introduced national volume criteria and relied on yearly hospital reported data for information on compliance. In the second era 'contract and control' (2009–2017), the effects of market-oriented reform became more evident. The Dutch government intervened in the market and health insurers introduced selective contracting. Medical professionals were prompted to reclaim the initiative. In the current era (2017-), a return of trust in self-regulation seems visible. The number of low-volume hospitals performing complex surgeries in the Netherlands has decreased and research has shown improved outcomes as a result. Conclusions: Based on the Dutch experience, the following lessons can be useful for other health care systems: 1. professionals should be in the lead in the development of national quality standards, 2. external pressure can be helpful for professionals to take the initiative and 3. volume remains a controversial quality measure. Future research and policies should focus on the underlying mechanism of volume-outcome relationships and overall effects of volume-based policies.